1990
DOI: 10.1021/ic00331a022
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the metal NMR chemical shift. Molybdenum complexes

Abstract: The 95Mo NMR chemical shift of the molybdenum complexes Mo04_"X"2-(X = S, Se; = 0-4) is studied theoretically with the ab initio molecular orbital method. The calculated results are in quite good agreement with experiments, showing the reliability of the method used in this series of studies. The Mo chemical shift mainly reflects the change in the valence 4d orbitals of molybdenum caused by ligand substitution. A perturbation theoretical analysis reveals that this change is dictated by the stabilization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The chemical shift tensor can be determined by a sum of diamagnetic, paramagnetic and spin-orbit contributions [6,19,49,50]. Among them, the dominant contribution that induces the difference of the chemical shift between the two sites in fMo 16 g was the paramagnetic deshielding term.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical shift tensor can be determined by a sum of diamagnetic, paramagnetic and spin-orbit contributions [6,19,49,50]. Among them, the dominant contribution that induces the difference of the chemical shift between the two sites in fMo 16 g was the paramagnetic deshielding term.…”
Section: Resultsmentioning
confidence: 99%
“…NMR chemical shifts are widely used in analytical chemistry, and they contain a lot of information about the electronic structures of molecules. In most quantum-chemical methods, the NMR chemical shift of compound M is defined as the deviation of the nuclear magnetic shielding constant σ from that of the reference molecule: σ can be divided into a diamagnetic term (σ dia ) and a paramagnetic term (σ para ): where σ dia and σ para are the first-order and second-order terms in the second-order perturbation theory. , Plenty of efforts have been made during the past decades in the calculation of NMR chemical shifts. Nakatsuji et al have comprehensively investigated the electronic mechanisms of the multinuclear NMR chemical shifts of transition metal complexes. They found that the paramagnetic term is generally dominant in the NMR chemical shift and they proposed the d-hole and p-electron mechanisms. , In these mechanisms, the d-hole paramagnetic term is generated by back-donation of electrons from the metal d-orbitals to the ligand. Thus, the chemical shift increases with stronger electron-withdrawing ability of the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the GIAO-HF s values reveals almost constant diamagnetic contributions, s d (very similar to those obtained at the DFT levels), and the deviations of the d values can be traced back to a strong overestimation of the paramagnetic contributions, s p . The molybdate derivatives 1 ± 6 have been the subject of previous studies at the HF level which employed finite perturbation theory (FPT) [37] and the localized-orbitals-local-origin (LORG) approach. [38] While excellent agreement with the experimental values was found in the former study, the latter work revealed similar overestimations of the d values, as found here.…”
Section: Resultsmentioning
confidence: 99%